Accesul la educaţia continuă, factor generator de inovaţie socială - Stoica, Laura Gabriela (Calitatea Vieții, 2009)
This article analyzes the field of education from the perspective of social innovation and it stresses out the role of the life-long learning policies as example of innovative policies. Social innovation is approached at the level of public policies, being presented the role of the access policies to life-long learning as innovation enablers. The objectives of the educational policies, the value of the indicators and the level of the public expenditure in life-long learning lead to the conclusion that education is an innovation enabler at the level of the EU and a blocking factor in Romania. In this article I describe the existing situation in this field both at the EU level and in Romania, by trying to identify the explanatory factors for this situation in both social contexts.